(untitled) (Yearbook - Faculty of Economics, 2018)
The financial crisis in Brazil and Argentina in the 90s is the primary focus in this paper through which it’s intended to capture the different causes and factors that led to drastic changes and imbalances in the national economies of these two countries. Certainly, particular interest in this paper is the application of appropriate measures by the authorities in both economies in cooperation with the IMF to find a way out from that economic situation and which would be aimed to achieving economic growth. All this was based on the application of measures of ‘‘Real Plan’‘ in Brazil and ‘‘Convertibility Plan’‘ in Argentina which were intended to achieve the desired level of economic stability.